The effects of calcitonin on post‐orthodontic relapse in rats - Hussein Abid Ali Muhsin Alnajar; Dheaa H. Al Groosh (Wiley, 2021)
Abstract Objectives To determine the effects of systematic calcitonin administration on post‐orthodontic relapse in rat model. Material and methods This experimental animal model involved 36 male Wister rats. The maxillary right first molars were moved mesially, using a modified orthodontic appliance delivered 50 gm, for 14 days, retained for 4 days and left to relapse for 10 days. The study group was divided into three subgroups in which a single injection of calcitonin (20 IU/Kg), three injections of calcitonin (20 IU/Kg), each every other day, and normal saline were administered subcutaneously after orthodontic tooth movement has finished. The relapse ratio, histomorphometric analysis including osteoblasts, osteoclasts numbers and bone area and immunohistochemical analysis including the expression of receptor activator of nuclear factor kappa Β (RANK), receptor activator of nuclear factor kappa Β ligand (RANKL) and osteoprotegerin (OPG) were measured and assessed. Results The relapse ratio was significantly reduced in the three‐dose calcitonin group (28%) compared to the single dose calcitonin group (34%) and the control group (46%). This was accompanied by a nonsignificant increase in osteoblasts number and bone area in three‐dose calcitonin group and a nonsignificant reduction in osteoclast number. However, the immune histochemical expression of RANK, RANKL and OPG did not show statistically significant difference at the end of relapse period. Conclusions Systemic administration of three doses of calcitonin may minimize the relapse ratio in experimentally moved rat molars.